2021
DOI: 10.3390/su131910499
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Water Use Practices: Understanding and Awareness of Masters Level Students

Abstract: Present water consumption in the UK is unsustainable, with increasing societal and environmental pressures driving water stress. Personal use of water is a significant contributor to water demand and considering the number of universities and students in the UK the water use practices therein cannot be ignored. Therefore, this paper aims to deepen the theme of water consumption in the United Kingdom from the point of view of use practices for students. The originality in this research lies in better understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 82 publications
(167 reference statements)
0
10
0
Order By: Relevance
“…Assigning quotas, or command and control methods, can be used to facilitate efficient, predictable sharing of resources (Shi et al, 2014). They are considered to be quicker and easier to implement compared to exploring the use of alternative water resources (Hunt and Shahab, 2021), including recycling (Blackmore et al, 2020) or allowing market forces to influence multiple users of the resource (Munasinghe, 2010). However, studies have also found command and control methods to result in greater economic losses and therefore to be more expensive to society (Olmstead and Stavins, 2009;Luby et al, 2018).…”
Section: The Value Of Watermentioning
confidence: 99%
See 3 more Smart Citations
“…Assigning quotas, or command and control methods, can be used to facilitate efficient, predictable sharing of resources (Shi et al, 2014). They are considered to be quicker and easier to implement compared to exploring the use of alternative water resources (Hunt and Shahab, 2021), including recycling (Blackmore et al, 2020) or allowing market forces to influence multiple users of the resource (Munasinghe, 2010). However, studies have also found command and control methods to result in greater economic losses and therefore to be more expensive to society (Olmstead and Stavins, 2009;Luby et al, 2018).…”
Section: The Value Of Watermentioning
confidence: 99%
“…Water efficiency measures are frequently reliant on the adoption of technological changes. This has inherent risks in leading to technological lock-in (Markolf et al, 2018), has the potential to limit innovation (Olmstead and Stavins, 2009) and not lead to the expected savings due to behavioral changes (Olmstead and Stavins, 2009;Hunt and Rogers, 2014;Hunt and Shahab, 2021). It also has the potential to increase inequity due to a requirement for new technology to meet the restriction.…”
Section: The Value Of Watermentioning
confidence: 99%
See 2 more Smart Citations
“…However, implementing efficient irrigation practices with many individual users and diverse landscapes is challenging [25]. One approach is an educational solution; many water conservation programs and university extension programs seek to communicate optimum watering practices to water users, including proper timing and depth of irrigation as well as fertilizer application [26][27][28][29][30]. Another option is a technical solution; irrigation systems with automated soil moisture sensors may help reduce water use as the systems only irrigate when plants require water, reducing over-irrigation [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%